Ultrastructural aspects of the remodeling process of the Corpus albicans in the recent postmenopausal period - Focchi, Gustavo Rubino de Azevedo; Simões, Manuel de Jesus; Baracat, Edmund Chada; Lima, Geraldo Rodrigues de; Evêncio Neto, Joaquim (São Paulo Medical Journal, 1996)
To study the cytophysiology of the Corpus albicans in the recent postmenopausal period, the authors analyzed the ovarian ultrastructure of ten patients submitted to oophorectomy due to non-malignant gynecological diseases. Evidence of a remodeling process with connective tissue substitution of the corpora albicantia was observed. The remodeling process appears to depend on the activity of three essential cell types: the fibroblasts, which provide collagen synthesis; the macrophages, which phagocytize the flaky material; and the myofibroblasts, mainly located in the peripheral region of the corpora albicantia, which may have a retracting action on the remodeling site of the Corpus albicans.